A novel phosphoinositide kinase Fab1 regulates biosynthesis of pathogenic aflatoxin in Aspergillus flavus. Issue 1 (1st January 2021) - Yang, Mingkun; Zhu, Zhuo; Bai, Youhuang; Zhuang, Zhenhong; Ge, Feng; Li, Mingzhu; Wang, Shihua
ABSTRACT: Aspergillus flavus ( A. flavus ) is one of the most important model environmental fungi which can produce a potent toxin and carcinogen known as aflatoxin. Aflatoxin contamination causes massive agricultural economic loss and a critical human health issue each year. Although a functional vacuole has been highlighted for its fundamental importance in fungal virulence, the molecular mechanisms of the vacuole in regulating the virulence of A. flavus remain largely unknown. Here, we identified a novel vacuole-related protein in A. flavus, the ortholog of phosphatidylinositol-3-phosphate-5-kinase (Fab1) in Saccharomyces cerevisiae . This kinase was located at the vacuolar membrane, and loss of fab1 function was found to affect the growth, conidia and sclerotial development, cellular acidification and metal ion homeostasis, aflatoxin production and pathogenicity of A. flavus . Further functional analysis revealed that Fab1 was required to maintain the vacuole size and cell morphology. Additional quantitative proteomic analysis suggested that Fab1 was likely to play an important role in maintaining vacuolar/cellular homeostasis, with vacuolar dysregulation upon fab1 deletion leading to impaired aflatoxin synthesis in this fungus. Together, these results provide insight into the molecular mechanisms by which this pathogen produces aflatoxin and mediates its pathogenicity, and may facilitate dissection of the vacuole-mediated regulatory network in A. flavus .